2014
DOI: 10.5958/2230-732x.2014.01373.4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Abundance of Different Floral Visitors on Egyptian Clover (Trifolium AlexandrinumL.) and Correlation with Weather Parameters

Abstract: The temporal abundance of different floral visitors on Egyptian clover, Trifolium alexandrinum l. and correlation with weather parameters was studied at Forage Section, Department of Genetics and Plant Breeding, CCS, Haryana Agricultural University, Hisar during 2012 and 2013. The mean temporal abundance of A. dorsata was the maximum (4.90/m 2 /5 min.) followed by A. mellifera (2.69), H. armigera (2.24), Eristalinus spp. (1.59) and A. florea (1.20/m 2 /5 min.) during 2012. During 2013, A. dorsata abundance dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A previous study also revealed that higher abundance was found for solitary bees (Megachile sp.) in T. alexandrinum (Dimitrov et al, 2020) while most of the other studies have reported honey bees (A. dorsata and A. mellifera) as most abundant pollinators visiting T. alexandrinum flowers (Sharma and Singh, 2003;Singh et al, 2012;Jat et al, 2014;Latif et al, 2014). Moreover, previously some studies reported that solitary bees are more abundant in fodder crops i.e., lucerne and Jantar (Cane, 2002;Sajjad et al, 2009;Wang et al, 2009).…”
Section: Mean Values Sharing Similar Letters In Respective Columns Sh...mentioning
confidence: 94%
“…A previous study also revealed that higher abundance was found for solitary bees (Megachile sp.) in T. alexandrinum (Dimitrov et al, 2020) while most of the other studies have reported honey bees (A. dorsata and A. mellifera) as most abundant pollinators visiting T. alexandrinum flowers (Sharma and Singh, 2003;Singh et al, 2012;Jat et al, 2014;Latif et al, 2014). Moreover, previously some studies reported that solitary bees are more abundant in fodder crops i.e., lucerne and Jantar (Cane, 2002;Sajjad et al, 2009;Wang et al, 2009).…”
Section: Mean Values Sharing Similar Letters In Respective Columns Sh...mentioning
confidence: 94%
“…cerana was observed during 1700-1900, 1500-1700, 1500-1700 and 1500-1700 hours of the day, respectively. Nagpal (2016)23 and Jat et al (2013)16 also reported that A. florea spent the maximum time per flower (6.08 sec), which was followed by A. dorsata (3.41 sec), A.…”
mentioning
confidence: 94%